1998
DOI: 10.1094/pdis.1998.82.8.931
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Benomyl Resistance in Mycosphaerella fijiensis, Cause of Black Sigatoka of Banana, in Costa Rica

Abstract: Sixty-eight and eighty-six percent of monoascosporic isolates of Mycosphaerella fijiensis from two banana plantations in Costa Rica, in which benomyl was used for ≈10 years to control black Sigatoka, were resistant to benomyl in February and November 1994, respectively. No resistance to benomyl was detected in isolates collected during February 1994 from farms with no history of benomyl use that were located ≈50 km from the nearest banana plantations. Only 1% of isolates was resistant to benomyl in a sample ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 8 publications
0
15
1
1
Order By: Relevance
“…Koenraadt et al (1992) identified strains of Venturia inaequalis resistant to benomyl in an orchard more than 10 years after benomyl use had been discontinued. In Mycosphaerella fijiensis from banana plantations where benomyl had been used for approximately 10 years to control black Sigatoka disease, 86% of isolates were resistant to benomyl, whereas no resistance was detected in isolates collected from plantations with no history of benomyl use (Romero and Sutton, 1998). In C. cereale causing turfgrass anthracnose, the difference in the prevalence of benomyl resistance among sampling sites also reflected the cumulative effects of benomyl use (Wong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Koenraadt et al (1992) identified strains of Venturia inaequalis resistant to benomyl in an orchard more than 10 years after benomyl use had been discontinued. In Mycosphaerella fijiensis from banana plantations where benomyl had been used for approximately 10 years to control black Sigatoka disease, 86% of isolates were resistant to benomyl, whereas no resistance was detected in isolates collected from plantations with no history of benomyl use (Romero and Sutton, 1998). In C. cereale causing turfgrass anthracnose, the difference in the prevalence of benomyl resistance among sampling sites also reflected the cumulative effects of benomyl use (Wong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports showing local aspects of fungicide resistance in isolates of M. fijiensis collected in America and other parts of the world (Romero and Sutton, 1997, 1998; Chin et al , 2001; Pérez et al , 2003; Vawdrey and Grice, 2005; Amil et al , 2007). However in Mexico, a few studies focussed on the current situation of fungicides resistance in M. fijiensis populations have been conducted (Manzo-Sánchez et al , 2012; Martínez-Bolaños et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Benomyl (a systemic benzimidazole fungicide) was used extensively in the 1970s to 1990s for control of black Sigatoka in many countries, but was gradually losing its efficacy because of expanding resistant fungal populations, particularly in some Latin American locations (Stover, 1977; Rodríguez & Jiménez, 1985; Romero & Sutton, 1998). Given that the introduction of the disease to Africa is considered to have originated from South East Asia via Central America (Rivas et al ., 2004), it was of interest to investigate whether the pathogen population studied here contained individuals harbouring resistance to this fungicide.…”
Section: Discussionmentioning
confidence: 99%